The Experience Of Students at SMP Negeri 1 Jeumpa In learning English Vocabulary Through Visual Video Media: Penelitian - Meutia Iman Fariha; Meristika Moetia (Jurnal Pustaka Cendekia Pendidikan, 2026)
This study explores the experiences of seventh-grade students at SMP Negeri 1 Jeumpa in learning English vocabulary through visual video media, focusing on their impressions, understanding, and challenges. The study is grounded in Mayer's Cognitive Theory of Multimedia Learning, which suggests that combining verbal and visual information enhances meaningful learning. Using a descriptive qualitative approach, data were collected through semi-structured interviews with ten purposively selected seventh-grade students and analyzed thematically using NVivo 12. The findings revealed one major theme, students' experiences of learning vocabulary through visual video media, with three subthemes: positive impressions, improved understanding, and learning challenges. Students generally perceived visual videos as enjoyable and motivating, helping them improve vocabulary retention, pronunciation, and comprehension. They also reported that the combination of images and audio made new vocabulary easier to understand and remember. However, they encountered challenges, including unfamiliar vocabulary, pronunciation difficulties, and videos that were too long or too fast. The study concludes that visual video media can effectively support English vocabulary learning when accompanied by appropriate video selection, suitable pacing, and teacher guidance. The findings also support Mayer's Cognitive Theory of Multimedia Learning and provide practical implications for English teachers.